A novel active snubber cell for soft-switched isolated PWM half-bridge converter - Bodur, Haci; Yesilyurt, Huseyin; Akboy, Erdem; Ting, Naim Suleyman (SPRINGER, 2020)
This paper introduces a novel modular active snubber cell for isolated half-bridge converters with ease of control. The novel snubber cell can achieved soft switching for all semiconductors at the proposed converter. The switches in the converter are derived simultaneously by the normal pulse-width modulation signals. The introduced snubber cell has a quite simple structure and ease of control. In this converter, the main switches turn on with zero current switching and turn off with zero voltage switching. Besides, there is no extra voltage stresses on the power elements. The proposed half-bridge DC-DC converter is analyzed in detail and its theoretical analysis is verified with a prototype having 50 A-25 V output values at 80 kHz frequency.
Keywords: Half-bridge; DC-DC converter; Soft switching; Snubber cell; BOOST CONVERTER; ZVS; DESIGN; IMPLEMENTATION; RECTIFIER; INVERTER; VOLTAGE; Engineering